ANEKA PANGAN OLAHAN REBUNG SEBAGAI ALTERNATIF PENDAPATAN EKONOMI IBU RUMAH TANGGA - ida waridah; Perdinandus Hermanto; Elvia Rahmawati; Yeni Adelia Rahmani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Abstract: Empowering housewives well, able to produce a product that has economic value so that it will be able to improve the economy of their family. Lingkar Indah Village is a village with a fertile land category with one of the most commodities being bamboo shoots. The lack of ability and knowledge of the community makes these natural resources have not been utilized optimally. Bamboo shoots are a commodity that has an economic opportunity, which can be used as a processed food product that has the potential to develop agribusiness and has a high selling value. The forms of PkM activities are: socialization and introduction of bamboo shoot processing, teaching, and application. The implementation of PkM runs quite effectively and is very beneficial for participants. The results of PkM activities are: increasing public knowledge and motivating them to become entrepreneurs through various processed bamboo shoots, knowing and understanding the importance and benefits of entrepreneurship, being able to be more skilled and creative in making processed bamboo shoots, knowing how to package processed bamboo shoots products, and knowing efficient strategies in marketing processed bamboo shoots products.Keywords: Food, Bamboo Shoots, Economy, Housewives